Three-dimensional advective flows in a horizontal square cross-section cylinder with adiabatic lateral walls - Lyubimova, Tatyana Petrovna; Nikitin, Dmitriy Alexeevich (Computational Continuum Mechanics, 2011)
Three-dimensional advective flows in a horizontal square cross-section cylinder with adiabatic lateral walls subjected to a homogeneous longitudinal temperature gradient are investigated numerically. It is shown that the flow structure strongly depends on the Grashof number, the channel length and the Prandtl number. Depending on these parameters, the flow can have different symmetry forms and time-varying behavior. It has been found that the transition to oscillatory modes can be implemented in two ways: with preliminary symmetry-breaking (fork bifurcation) or without symmetry form change. The parameter range, in which only the fork bifurcation takes place and oscillatory modes do not appear, is determined.
Keywords: horizontal cylinder; advective flows; adiabatic walls; three-dimensional nonlinear regimes